The Effect of Soaking Time and Temperature of Acetic Acid Solution to the De-crease of Calcium Oxalate Levels in Porang Tubers - Ratih Kusuma Wardani; Djamilah Arifiyana (Future Science)
Porang is one of the tubers that grow easily in the plains of Indonesia, one of which is in the Madiun city area, East Java. Porang tubers can be used in various sectors, namely in food processing. Porang tubers are used as the basic material for making food, such as flour. However, porang tubers contain high levels of calcium oxalate. It can cause itchy tongue and throat. This study aimed to determine the effect of temperature and soaking time of porang tubers in 5% acetic acid solution. Soaking the porang tuber sample at 60°C had the greatest decrease percentage in calcium oxalate, which was 53.91%. Soaking the porang tubers for 60 minutes also gave the largest reduction percentage in calcium oxalate, namely 42.54%.